Major histocompatibility complex variation is similar in little brown bats before and after white‐nose syndrome outbreak. Issue 18 (31st August 2020) - Yi, Xueling; Donner, Deahn M.; Marquardt, Paula E.; Palmer, Jonathan M.; Jusino, Michelle A.; Frair, Jacqueline; Lindner, Daniel L.; Latch, Emily K.
Abstract: White‐nose syndrome (WNS), caused by the fungal pathogen Pseudogymnoascus destructans (Pd), has driven alarming declines in North American hibernating bats, such as little brown bat ( Myotis lucifugus ). During hibernation, infected little brown bats are able to initiate anti‐Pd immune responses, indicating pathogen‐mediated selection on the major histocompatibility complex (MHC) genes. However, such immune responses may not be protective as they interrupt torpor, elevate energy costs, and potentially lead to higher mortality rates. To assess whether WNS drives selection on MHC genes, we compared the MHC DRB gene in little brown bats pre‐ (Wisconsin) and post‐ (Michigan, New York, Vermont, and Pennsylvania) WNS (detection spanning 2014–2015). We genotyped 131 individuals and found 45 nucleotide alleles (27 amino acid alleles) indicating a maximum of 3 loci (1–5 alleles per individual). We observed high allelic admixture and a lack of genetic differentiation both among sampling sites and between pre‐ and post‐WNS populations, indicating no signal of selection on MHC genes. However, post‐WNS populations exhibited decreased allelic richness, reflecting effects from bottleneck and drift following rapid population declines. We propose that mechanisms other than adaptive immunity are more likely driving current persistence of little brown bats in affected regions. Abstract : We tested the hypothesis of white‐nose syndrome (WNS) selection on MHC genes of hibernating bats by comparing the MHC class II DRB gene in little brown bats sampled from sites having different exposure histories to Pd, the fungus that caused WNS. We compared the WNS‐naive population in Wisconsin and the multi‐year post‐WNS population in New York and Vermont and found similar MHC variation, including the same most common alleles, comparable allelic diversity, and insufficient genetic differentiation, all indicating the lack of WNS selection on MHC genes. Our results indicated that the studied little brown bat populations may not rely on adaptive immunity to persist under WNS, and other mechanisms such as the physiological and behavioral changes found in recent studies may be more effective under WNS.